giúp bài 2 thôi ạ
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a;b bạn tự làm nhé, hđt số 3 là ra
c, \(\sqrt{7-2\sqrt{10}}-\sqrt{5-2\sqrt{6}}-\left(\sqrt{5}-\sqrt{3}\right)\)
\(=\sqrt{\left(\sqrt{5}-\sqrt{2}\right)^2}-\sqrt{\left(\sqrt{3}-\sqrt{2}\right)^2}-\sqrt{5}+\sqrt{3}\)
\(=\sqrt{5}-\sqrt{2}-\sqrt{3}+\sqrt{2}-\sqrt{5}+\sqrt{3}=0\)
Bài 2g
`\(\frac{\sqrt{2}}{\sqrt{1+\sqrt{2}}-1}-\frac{\sqrt{2}}{\sqrt{1+\sqrt{2}}+1}\)
\(=\frac{\sqrt{2}\sqrt{1+\sqrt{2}}+\sqrt{2}-\sqrt{2}\sqrt{1+\sqrt{2}}+\sqrt{2}}{1-\sqrt{2}-1}\)
\(=\frac{2\sqrt{2}}{-\sqrt{2}}=-2\)
\(P=\sqrt{2}\left(\sqrt{8}-2\sqrt{8}\right)+2\sqrt{6}\)
\(=\sqrt{2}\left(2\sqrt{2}-4\sqrt{2}\right)+2\sqrt{6}\)
\(=4-8+2\sqrt{6}=-4+2\sqrt{6}\)
\(=x^2+4\sqrt{3}x-4\sqrt{3}-1\)
\(=\left(x^2-1\right)+\left(4\sqrt{3}x-4\sqrt{3}\right)\)
\(=\left(x-1\right)\left(x+1\right)+4\sqrt{3}\left(x-1\right)\)
\(=\left(x-1\right)\left(x+1+4\sqrt{3}\right)\)